PERFORMANCE OF SAND SHEET ASPHALT MIXTURE INCORPORATING RECLAIMED ASPHALT PAVEMENT - Thanaya, I N. Arya; Purbanto, I G. Raka; Wirahadi, A.A.G. (Jurnal HPJI, 2015)
Abstract This paper presents lab works on sand sheet asphalt mixture utilizing reclaimed asphalt pavement (RAP) as the main material. Sand sheet asphalt mixture is dedicated for low to medium trafficked road pavement. The asphalt content of the RAP was initially extracted. A proportioned sand and rice husk ash was added to meet the aggregate grading. The asphalt used was AC 60/70, the most widely available type of asphalt in market. The asphalt content of the RAP was 6.7%. The mixture was produced in hot mix procedure with compaction of 2 x 50 Marshall Blow. The optimum asphalt content was 7.7% (including the asphalt content in the RAP). The properties of the samples were found well met the specification in Indonesia, i.e. the stability was 1501.5 kg, flow 2.96 mm, Marshall Quotient 476.31 kg/mm, VIM 4.916% , VFB 75.55%, VMA 20.10%, and retained stability 94%. Keywords: performance, sand sheet, RAP, rice husk ash  Abstrak Makalah ini mempresentasikan pekerjaan laboratorium Sand Sheet Asphalt dengan memanfaatkan perkerasan beraspal bekas (RAP) sebagai material utama. Sand Sheet Asphalt dapat digunakan untuk perkerasan jalan dengan arus lalulintas ringan hingga sedang. Langkah awalnya dengan melakukan ekstraksi asphalt content pada RAP. Kemudian secara proporsi pasir dan sekam  ditambahkan untuk mendapatkan komposisi butiran agregat. Aspal yang digunakan adalah AC 60/70 yang pada umumnya tersedia di pasaran. Kandungan aspal pada RAP sebesar 6,7%. Campuran dihasilkan dengan prosedur campuran beraspal panas dengan pemadatan 2 x 50 Marshall blows. Sedangkan kandungan optimal aspal  sebesar 7,7% (termasuk kadar aspal dalam RAP). Properti sampel ditemukan memenuhi spesifikasi yang berlaku di Indonesia, yaitu stabilitas 1501,5 kg, flow 2,96 mm, Marshall Quotient 476,31 kh/mm, VIM 4,916%, VFB 75,55%, VMA 20,10%, dan stabilitas sisa 94%. Kata-kata kunci: kekuatan, sand sheet, perkerasan aspal bekas, sekam.